9/11 ten years after perspectives and problems - Utley, R. E. 1972- (Routledge Ashgate Publishing, 2012)
Investigates a range of international responses to the events of 9/11, to evaluate their consistency over time; to analyse their long-term significance and impact and to consider both their implications for the international security agenda and the prospects for international cooperation in addressing the challenges posed.